(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The heat exchanger (HE) is a device that is used to complete the process of heat transfer between different matters without direct mixing. Therefore, it is of great importance in the transfer of energy and the completion of various energy transition processes. In the processes of HE between different energy systems, many factors influence and play a major and important role in the efficiency of transformation and exchange in forms of energy, such as the length, the material type, the exchange fluid, the surrounding environment, and many other factors. In this work, the effect of the HE temperature of the parallel and counter flow HEs was investigated based on the use of computer simulation programs. There was a significant impact of the exchange factors, especially the length of the HEs in both the parallel and counter-flow HEs, on the quality and efficiency of the HE and the temperature distribution, A steady-state conjugate heat transfer (CHT) model is coupled with computational fluid dynamics (CFD) analysis. In addition, the temperature profile and velocity streamline are also checked to analyze the fluid flow behavior of the radiator. With large temperature differences, variations in fluid properties due to temperature lead to changes in the surface heat transfer coefficient (SHTC). The combined effects of SHTC and temperature difference determine the heat transfer performance. the heat transfer performance and standard deviation of outlet temperature distribution. The aim of this paper is to investigate numerically the influence of variable fluid viscosity on thermal characteristics of plate heat exchangers for counter-flow and steady-state conditions. A finite difference method has been used to calculate the temperature distribution and thermal performance of the exchanger. Water is used as the hot liquid being cooled in the side channels, while a number of working fluids whose viscosity variation versus temperature is more severe were used as the cold fluid being heated in the central channel. The temperature distributions of both streams have been plotted along the flow channel for all the above combination of working fluids. It is found that the overall heat transfer coefficient varies linearly with respect to either cold or hot fluid temperature within the temperature ranges applied in the paper. The exchanger effectiveness is not significantly affected when either the temperature dependent viscosity is applied or the nature of cold liquid is changed. paper contains a new method of numerical solution of energy balance equations for the thermal control volumes bounded by two plates.